Cooperative answering and Inferential Erotetic Logic - Łupkowski, Paweł (Polish Society for Cognitive Science, 2010)
This paper addresses the issue of applicability of erotetic search scenarios, a tool developed within Inferential Erotetic Logic, in the area of cooperative answering for databases and information systems. Short descriptions of cooperative answering and Erotetic Search Scenarios are given. Some basic cooperative answering phenomena are modeled within the framework of Erotetic Search Scenarios.
Keywords: Cooperative answering; Erotetic logic; Information systems; Databases